(untitled) (Asian Journal of Agriculture, 2023)
Abstract. Saimon AH, Sultana S, Mannan MA, Mamun AA. 2023. Assessment of genetic diversity among sweet potato varieties through RAPD markers in the Southern coastal region of Bangladesh. Asian J Agric 7: 116-121. Sweet potato (Ipomoea batatas (L.) Lam.) is the sixth most significant food crop. Evaluating this crop’s genetic diversity is crucial for food security and preserving agricultural genetic resources. Bangladesh is South Asia’s second-largest sweet potato producer, but little is known about the genetic diversity of this crop there. The study aimed to assess the genetic diversity among six sweet potato varieties (Five BARI-released sweet potato varieties: BARI Misty Alu-10, BARI Misty Alu-11, BARI Misty Alu-12, BARI Misty Alu-14, BARI Misty Alu-15, and a local cultivar) using RAPD marker in the Southern coastal region of Bangladesh. Six primers were utilized to determine the polymorphic and monomorphic bands. Data was analyzed using the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) dendrogram and Principal Component Analysis (PCA). Thirty-seven polymorphic bands were found, with an average of 3 polymorphic and 3.17 monomorphic bands. Primer OPM-02 showed the highest polymorphic bands (6). The results showed that BARI Misty Alu-10 and BARI Misty Alu-15 had the most genetic diversity, at 37%. The average polymorphism percentage was 44.88%. The dendrogram featured two distinct clusters that showed BARI Misty Alu-12, the most distant variety. The clustering pattern corresponded with PCA, demonstrating that BARI Misty Alu-12 had the most genetic variation (81.36%).